Analisis Perubahan Penggunaan Lahan Kawasan Kumuh Kecamatan Kandis Kabupaten Siak Tahun 2014 dan 2023 - Siregar, Dina Khoriah; Yulfa, Arie (Al-DYAS, 2024)
This research aims to identify the causes of land use change in the slum areas of Kandis Sub-district, Siak Regency, and analyze land use change from 2014 to 2023 using information maps. The method used is descriptive quantitative, with data analysis techniques based on weighting the quality of slum areas through geographic information systems (GIS) using GIS applications to identify location, distance, and settlement patterns. Sampling was done through proportional stratified random sampling. Data collection used primary data in the form of interviews and secondary data in the form of documentation studies. The results showed that: (1) The causes of land use change in Kandis Sub-district slum areas include an increase in population density every year, narrow spacing between buildings (1.5 to 3 meters), lack of clean water infrastructure, inadequate drainage, inadequate toilet conditions, and lack of waste disposal facilities. Community income is also low, below Rp. 1,000,000 per month. (2) The area of the slum area has increased significantly, from 0.27 Ha in 2014 to 9.6 Ha in 2023.